Grain size in Hashilan Wetland sediment core, western Iran - Safaierad, Reza; Zolitschka, Bernd (In: Safaierad, Reza; Zolitschka, Bernd; Djamali, Morteza; Dupont, Lydie M; Vogt, Christoph; Matthews, Roger (2023): Pollen, grain size, loss-on-ignition, elemental and mineralogical composition, magnetic susceptibility and radiocarbon measurements in Hashilan Wetland sediment core [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.956292, 2023)
For grain size, prior to grain size analyses, OM was removed by H2O2 (30 %) and carbonates were destroyed with HCl (10 %) from samples. For dispersion, 20 ml of Calgon [(NaPO3)n] was added and agitated overnight. On the next day, analyses were performed with a laser diffraction particle-size analyzer (Beckman Coulter LS 200) after ultrasonic treatment for 30 s. Each sample was measured at least four times for 60 s until a stable distribution was reached. Thereafter, the arithmetic mean was calculated for the best three sample runs. Grain size distributions and all statistical grain size parameters were calculated from the output of the LS 200 as geometric graphical measures according to Folk and Ward (1957) with the MS Excel-based macro Gradistat, Version 8.0 (Blott and Pye, 2001). Analyses were carried out in the GEOPOLAR lab at the University of Bremen.
Keywords: Atmospheric dust; Grain Size; Holocene climate; loss on ignition; Magnetic susceptibility; Pollen; Vegetation dynamics; XRD; XRF